What to expect when you're expecting - Murkoff, Heidi Eisenberg; Mazel, Sharon (New York : Workman Pub., 2008)
Cuts through the confusion surrounding pregnancy and birth by debunking dozens of myths that mislead parents, offering explanations of medical terms, and covering a variety of issues including prenatal care, birth defects, and amniocentesis
Foreword to the fourth edition / Charles J. Lockwood -- Introduction : why this book was born again, again -- pt. 1. First things first: ch. 1. Before you conceive ; ch. 2. Are you pregnant? ; ch. 3. Your pregnancy profile ; ch. 4. Your pregnancy lifestyle ; ch. 5. Nine months of eating well -- pt. 2. Nine months & counting : from conception to delivery: ch. 6. The first month : approximately 1 to 4 weeks ; ch. 7. The second month : approximately 5 to 8 weeks ; ch. 8. The third month : approximately 9 to 13 weeks ; ch. 9. The fourth month : approximately 14 to 17 weeks ; ch. 10. The fifth month : approximately 18 to 22 weeks ; ch. 11. The sixth month : approximately 23 to 27 weeks ; ch. 12. The seventh month : approximately 28 to 31 weeks ; ch. 13. The eighth month : approximately 32 to 35 weeks ; ch. 14. The ninth month : approximately 36 to 40 weeks ; ch. 15. Labor and delivery -- pt. 3. Twins, triplets & more : when you're expecting multiples: ch. 16. Expecting more than one -- pt. 4. After the baby is born: ch. 17. Postpartum : the first week ; ch. 18. Postpartum : the first 6 weeks -- pt. 5. For dads: ch. 19. Fathers are expectant, too -- pt. 6. Staying healthy when you're expecting: ch. 20. If you get sick ; ch. 21. If you have a chronic condition -- pt. 7. The complicated pregnancy: ch. 22. Managing a complicated pregnancy ; ch. 23. Coping with pregnancy loss
Includes index
Keywords: Pregnancy; Childbirth; Postnatal care; Labor, Obstetric; Popular Works